Influence of Baseline Kinesiophobia Levels on Treatment Outcome in People With Chronic Spinal Pain. Issue 6 (22nd February 2021) - Van Bogaert, Wouter; Coppieters, Iris; Kregel, Jeroen; Nijs, Jo; De Pauw, Robby; Meeus, Mira; Cagnie, Barbara; Danneels, Lieven; Malfliet, Anneleen
Abstract: Background: Pain neuroscience education (PNE) combined with cognition-targeted exercises is an effective treatment for people with chronic spinal pain (CSP). However, it is unclear why some patients benefit more from this treatment. We expect that patients with more pronounced maladaptive pain cognitions, such as kinesiophobia, might show poorer treatment responses. Objective: The objective of this study was to assess the influence of baseline kinesiophobia levels on the treatment outcomes of PNE combined with cognition-targeted exercises in people with CSP. This study was a secondary analysis of a multicenter, double-blind, randomized controlled trial. Methods: Outcome measures included a numeric rating scale for pain (NRS), the Pain Disability Index (PDI), quality of life (Medical Outcomes Study 36-Item Health Survey [SF-36]), Pain Catastrophizing Scale (PCS), and Pain Vigilance and Awareness Questionnaire (PVAQ). Regression models were built using treatment (PNE plus cognition-targeted exercises or neck/back school plus general exercises), baseline scores on the Tampa Scale for Kinesiophobia (TSK), and time (in months) as independent variables. Results: A significant 3-way interaction effect was found for the models of PDI, PCS, PVAQ, and the SF-36 mental domain, with estimates of −0.01, −0.01, −0.01, and 0.07, respectively. A significant effect of baseline TSK scores was found for the physical domain of the SF-36 (estimate = −3.16). For the NRS, no significant effect of baseline TSK scores was found. Conclusion: Our findings indicate that PNE plus cognition-targeted exercises can successfully decrease the unfavorable influence of pretreatment kinesiophobia on disability, mental health, pain catastrophizing, and hypervigilance over time in people with CSP. Nevertheless, higher scores in pretreatment kinesiophobia might still be a key factor for the lack of improvement in pain catastrophizing and hypervigilance following treatment. Regardless of the followed treatment program, pretreatment kinesiophobia was also shown to significantly influence physical health in people with CSP. Impact: This study provides novel insight into the unfavorable influence of kinesiophobia on treatment outcomes in people with CSP, and how PNE plus cognition-targeted exercises can limit this impact. Because this is one of the first studies to research possible predictors of this experimental treatment, its findings motivate further exploration of other possible influencing factors for treatment success of PNE plus cognition-targeted exercises. Lay Summary: People with chronic spinal pain and high levels of fear of movement were found to have worse treatment outcomes compared to people with low levels of fear of movement. However, our experimental treatment, which includes pain neuroscience education combined with exercise therapy that reintroduces specific movements patients might fear, can decrease this negative influence of fear of movement in these patients.